Long‐term results of liver transplantation for maple syrup urine disease: A single‐center experience in Turkey. (1st January 2023) - Aras, Arzu; Avanaz, Ali; Inan Aydemir, Nurel; Kayaalp, Ece; Ulgen Tekerek, Nazan; Kisaoglu, Abdullah; Demiryilmaz, Ismail; Soyucen, Erdogan; Dursun, Oguz; Yilmaz, Aygen; Artan, Reha; Aydinli, Bulent
Abstract: Objectives: Maple syrup urine disease (MSUD) is an autosomal recessive inherited disorder. Despite the advances in medical nutrition therapies, classical phenotype causes severe neurological disorders and sudden death. It is known that MSUD patients do not experience metabolic attacks despite their free diet after liver transplantation (LT). This study aims to reveal the long‐term results, development, mental, motor, intellectual and nutritional status of MSUD patients who underwent LT. Methods: The data of 12 patients who underwent deceased donor (5 recipients) and living donor liver transplantation (7 recipients) were retrospectively analyzed. The age, genotype, psychometric and mental status, development, BCAA values, type of LT, donor‐recipient proximity, complications, and survival were assessed. Results: There were 4 (33%) girls and 8 (67%) boys. The mean current age was 9.33 ± 4.58 years. The mean follow‐up time was 3 ± 2.5 years. The repeated measures of leucine and isoleucine values revealed that there were no significant differences from the pre‐LT to post‐LT 1‐year. The protein‐restricted nutrition was switched to a free diet when oral intake was opened after LT. None of the recipients experienced metabolic attacks after the living donor or deceased donor LT. The 1‐, 3‐, and 5‐year survival rate of the patients is 83.3%. There was no significant difference in survival between living and deceased donor liver transplantation. Conclusions: Liver transplantation is a treatment option for MSUD in proper conditions to save the patient life, increase the quality of life, and provide essential amino acids with free diet intake for growth and development.